Four new species of Aphelinidae (Hymenoptera: Chalcidoidea) from Mexico - Myartseva, Svetlana Nikolaevna; Ruíz-Cancino, Enrique; Coronado-Blanco, Juana María (Zootaxa, 2013)
Four new species of Encarsia Förster (Hymenoptera: Aphelinidae) from Mexico are described—E. albata Myartseva sp. n. (State of Nuevo León), E. barracas Myartseva sp. n. (State of Baja California Sur), E. chichenitza Myartseva sp. n. (State of Yucatán) and E. elenae Myartseva sp. n. (State of Tamaulipas). A key to the species of Encarsia in Mexico pub-lished in 2012 is modified to include the newly described species.